Praktik Penggunaan Herbal pada Ibu Menyusui di Kelurahan Karangklesem Purwokerto Selatan Purwokerto - -, Sumarni; Anasari, Tri (Universitas Harapan Bangsa Purwokerto, 2019)
Abstract The effect of herbal consumption on breastfeeding mothers is often associated with breast milk production and recovery of maternal stamina after giving birth. Herbs have a composition that helps the process of postpartum recovery and increase milk production. Herbal plants that have a positive influence in breastfeeding mothers and are allowed to be consumed include: long bean / violet leaves, banana heart, katuk leaves, palm juice, papaya leaves, bitter melon leaves, basil seeds, cumin seeds. The purpose of this study was to determine the practice of using herbal plants in nursing mothers in South Purwokerto District. Research methods: This study used descriptive research with a retrospective time approach. Total population of 40 mothers in Karangklesem South Purwokerto. Sampling technique with random sampling. Data analysis uses univariate frequency distribution analysis. The results showed that most breastfeeding mothers used herbs during lactation and types of herbs used included: turmeric, ginger, ginger, kencur, Javanese acid, papaya leaves, betel leaves, kemukus, katuk leaves. Conclusion most breastfeeding mothers use herbs during lactation. Keywords: The practice of using herbs, breastfeeding mothers